An update on the safety of ixazomib for the treatment of multiple myeloma. Issue 9 (2nd September 2022) - Goel, Utkarsh; Kumar, Shaji
ABSTRACT: Introduction: Treatment options for multiple myeloma (MM) have rapidly expanded over the past few years with several newly approved drugs. While there is need to explore treatments that lead to longer responses and survival, special consideration should be given on reducing treatment burden, reducing toxicities, and improving quality of life. Ixazomib is the first oral proteasome inhibitor for the treatment of MM, combining clinical efficacy with a favorable safety profile. Areas covered: Here, we discuss the clinical efficacy and safety of ixazomib. Pharmacokinetic considerations, management of common toxicities, and the impact of the drug on the current and future treatment strategies are also discussed. Expert opinion: Ixazomib is an effective and welltolerated MM drug. It is also being studied in combination with other newer agents. It does not have long-term cumulative toxicities, and the most adverse events are mild and manageable. These findings, along with the ease of oral administration, make it a possible option for long-term treatment approaches for MM patients, as well as in the frail/elderly patient population.